EFEK ANTIINFLAMASI KOMBINASI ASTAXANTHIN DENGAN VITAMIN E TERHADAP JUMLAH TROMBOSIT (Studi Eksperimental pada Tikus Putih Jantan Galur Wistar yang Diinduksi Karagenan) - Salsabila Tria Ramadhani; Sampurna (PT. Hasba Edukasi Mandiri, 2025)
Background: Inflammation is a defense reaction involving cells, mediators, and blood vessels, including platelets, to eliminate causes of cell damage. Carrageenan is a cause of cell damage that induces platelets through the NF-κB pathway by TLR-4 signaling. The combination of astaxanthin and vitamin E has anti-inflamatory effects characterized by a decrease in platelet count by suppressing NF-κB, COX-2, and ROS activity. Objective: This study aims to determine the effect of the combination of astaxanthin and vitamin E on platelet counts in male Wistar rats induced by carrageenan. Method: This study was experimental with a post-test only control group design. A total of 30 rats were adapted for 7 days with the same feed and drink, then the rats were divided into a normal group (n=10), a sick group (n=10), and a treatment group (n=10). The treatment group was given a combination of 0.72 mg/kgBW astaxanthin and 24.1 mg/kgBW vitamin E. One hour later, the sick and treatment groups were given a 0.1 mL injection of 1% carrageenan and waited for 24 hours, while the normal group was only given standard feed. The platelet count was measured using a hematology analyzer. The data were analyzed using the Shapiro Wilk test, Levene Statistic, Kruskal Wallis, and followed by the Mann Whitney Post Hoc test. Result: The mean platelet count was 144.86 × 10³/µL in the normal group, 316.79 × 10³/µL in the sick group, and 214.07 × 10³/µL in the treatment group. The results of the normality test KP (p<0.05), KN and KS (p>0.05), homogeneity (p<0.05), Kruskal Wallis (p<0.05) were significantly different, and the Post Hoc Mann Whintney (p<0.05) showed significant differences between all groups. Conclusion: Data analysis revealed an anti-inflammatory effect of the combination of astaxanthin and vitamin E in carrageenan-induced rats.